Curcumin-enhanced chemosensitivity of FDA-approved platinum (II)-based anti-cancer drugs involves downregulation of nuclear endonuclease G and NF-κB as well as induction of apoptosis and G2/M arrest. (May 2014) - Wang, Ying-Ti; Liu, Hsiao-Sheng; Su, Chun-Li
Abstract Curcumin, an active natural compound in turmeric and curry, has been reported to exhibit anti-cancer effect. Cisplatin, carboplatin and oxaliplatin are used to treat various types of cancers. However, acquired resistance and toxicities are observed. Here, the addition of curcumin significantly increased cytotoxicity of the anti-cancer drugs on human colorectal cancer HT-29 cells, producing synergistic (cisplatin and carboplatin) and additivity (oxaliplatin) effects. Treatments in combination with curcumin resulted in a significantly increased induction of apoptosis and occurrence of G2/M arrest. Nuclear apoptosis-inducing factor (AIF), EndoG and NF-κB were elevated by anti-cancer drugs, suggesting the involvement of AIF and EndoG. The addition of curcumin suppressed nuclear AIF and EndoG and reversed anti-cancer drugs-induced NF-κB expression, suggesting the association of EndoG and NF-κB in curcumin-enhanced chemosensitivity. Therefore, the intake of foods rich in curcumin or curcumin-containing supplements should be taken into consideration for patients receiving chemotherapy to optimize the outcome of treatments.